Transformational development in a changing context: A Latin American perspective - Zeeland, Angelique J. W. M. van (HTS teologiese studies, 2016)
This article analyses the challenges for the strategies and practices of transformational development in a changing context. This reflection is based on contributions received during the process of dialogues and regional consultations, realised from August 2012 until March 2014, of the ACT Alliance, an international coalition of churches and faith-based organisations (FBOs) working in the areas of humanitarian response, development and advocacy. The main processes that affect the changing development context are addressed, such as the ongoing globalisation as well as the consequences, mainly regarding the shrinking space for civil society. It discusses the concepts of human development and of transformational development, based on a people-centred development vision, a human rights-based approach and advocacy, which addresses the root causes and effects of poverty, inequality and injustice. Transformational development practices, from Latin America, are presented and analysed. The article concludes that the changing development context also offers opportunities, especially regarding regional and global alliances of FBOs, civil society organisations and of social movements.